Building Resilient Financial Performance: a Case Study of Indonesian Islamic Banks in The Perspective of SDGs - Asy-syihab, Moch. Nauval; Rafiuddin, Muhammad; Ashari, Nesha Rizky; S. Kau, Najwa Nainawa (UIN Sunan Kalijaga Yogyakarta, 2024)
Research Aims: This study examines the impact of financial indicators—Non-Performing Financing (NPF), Financing to Deposit Ratio (FDR), Capital Adequacy Ratio (CAR), and Operating Expenses to Operating Income (BOPO)—on the Return on Assets (ROA) of Indonesian Islamic banks, aiming to contribute to SDG 8 by enhancing understanding of financial performance factors. Methodology: A quantitative approach is applied using secondary data from Indonesia's Financial Services Authority (OJK) covering 2018–2022. Multiple linear regression analysis identifies significant factors influencing ROA. Research Findings: The study finds that NPF, FDR, CAR, and BOPO all significantly affect ROA. Specifically, while NPF has a positive but insignificant impact, FDR, CAR, and BOPO exhibit negative and significant effects on ROA, suggesting that Islamic banks should focus on credit quality, capital adequacy, and operational efficiency. Theoretical Contribution: This research provides novel insights by exploring the financial ratios' influence on ROA within Indonesian Islamic banks, contributing to the limited literature in this specific area and offering implications for the sector's sustainability in line with SDG 8. Research limitation and implication: The study is limited to secondary data from nine banks over five years. Future research could expand to more banks or explore other performance measures. The findings offer practical implications for improving the financial stability and growth strategies of Islamic banks.